Identification of a Novel Allosteric Inhibitory Site on Tryptophan Hydroxylase 1 Enabling Unprecedented Selectivity Over all Related Hydroxylases - Petrassi, Mike; Barber, Rob; Be, Celine; Beach, Sarah; Cox, Brian; D’Souza, Anne-Marie; Duggan, Nick; Hussey, Martin; Fox, Roy; Hunt, Peter; Jarai, Gabor; Kosaka, Takatoshi; et al. (Frontiers in Pharmacology, 2017)
Pulmonary arterial hypertension (PAH) has demonstrated multi-serotonin receptor dependent pathologies, characterized by increased tone (5-HT1B receptor) and complex lesions (SERT, 5-HT1B, 5-HT2B receptors) of the pulmonary vasculature together with right ventricular hypertrophy, ischemia and fibrosis (5-HT2B receptor). Selective inhibitors of individual signaling elements - SERT, 5-HT2A, 5HT2B and combined 5-HT2A/B receptors, have all been tested clinically and failed. Thus, inhibition of tryptophan hydroxylase 1 (TPH1), the rate limiting step in 5-HT synthesis, has been suggested as a more broad, and thereby more effective, mode of 5-HT inhibition. However, selectivity over non-pathogenic enzyme family members, tryptophan hydroxylase 2 (TPH2), phenylalanine hydroxylase (PH) and tyrosine hydroxylase (TH) has hampered therapeutic development. Here we describe the site/sequence, biochemical and biophysical characterization of a novel allosteric site on TPH1 through which selectivity over TPH2 and related aromatic amino acid hydroxylases is achieved. We demonstrate the mechanism of action by which novel compounds selectively inhibit TPH1 using surface plasma resonance and enzyme competition assays with both tryptophan ligand and BH4 co-factor. We demonstrate 15-fold greater potency within a human carcinoid cell line versus the most potent known TPH1/2 non-specific inhibitor. Lastly, we detail a novel canine in vivo system utilized to determine effective biologic inhibition of newly synthesized 5-HT. These findings are the first to demonstrate TPH1-selective inhibition and may pave the way to a truly effective means to reduce pathologic 5-HT and thereby treat complex remodeling diseases such as pulmonary arterial hypertension.